Production and investigation of Cu/thin intermediate tunnel-transparent dielectric oxide layer/n-Pb₀.₉₃₅Sn₀.₀₆₅Te₀.₂₄₃Se₀.₇₅₇/In Schottky barrier structures - Tkachuk, A.I.; Tsarenko, O.N.; Ryabets, S.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The high-planar epitaxial layers of n-Pb₀.₉₃₅Sn₀.₀₆₅Te₀.₂₄₃Se₀.₇₅₇ quaternary solid solutions, lattice matched with {111}BaF2 substrates, have been grown from bounded volume of supersaturated melt-solutions in the growth temperature region 773-873 K by the liquid phase epitaxy technique at a programmatic refrigeration rate of 0.1-0.2 K/min and a temperature reduction range of DT=5-10 K. The laboratory methodology of the production of Cu/δ-layer/n-Pb₀.₉₃₅Sn₀.₀₆₅Te₀.₂₄₃Se₀.₇₅₇ /In Schottky barrier structures by thermal vacuum deposition has been developed. The current- and farad-voltage characteristics of these structures have been measured at the 77 K, and the dependence of the diode electro-physical properties on the δ-layer width has been studied.